Prescription pattern of antimicrobial agents prescribed in outpatient department of dermatology in a tertiary care hospital in India - Shankpal, Pramod D.; Patil, Madhura P. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Skin diseases contribute largely to global disease burden. Antimicrobial agents are used for treatment of various skin diseases of microbial aetiology caused by fungi, bacteria, viruses and ectoparasites. The primary objective of this study was to study the prescription pattern of antimicrobial agents in dermatology, to provide insights into the disease patterns, profile of the drugs used and their rationality. Methods: Cross-sectional observational study was conducted in dermatology outpatient department of T. N. M. C. and B. Y. L. Nair Charitable Hospital, Mumbai for period of 6 months. 372 prescriptions containing an antimicrobial agent (AMA) were analysed. Demographic data, disease pattern, associated comorbidities and prescription details were recorded after taking written informed consent. Results: Fungal infections were the most common (48%) followed by bacterial infections (31%). The most encountered condition was dermatophytosis. Average number of AMA per prescription was 2.33±0.73. Percentage of AMA prescribed by generic name was 48%. Percentage of AMA prescribed from National list of essential medicines 2015 (NLEM) was 32.60%. 87.9% of AMA were prescribed as combination therapy and 12.10% were prescribed as monotherapy. The commonest prescribed drugs were antifungals followed by antibiotics. Topical creams were the commonest prescribed dosage form. Conclusions: The most common class of antimicrobial agents prescribed was antifungal agents. Prescribing combination of oral antimicrobials with topical antimicrobials was found to be high. This study provides a framework for continuous prescription audit of antimicrobials in an outpatient setting and thus can help in rational use of antimicrobials in dermatological prescribing.